Regrowth of Microcosm Biofilms on Titanium Surfaces After Various Antimicrobial Treatments - Han, Qi; Jiang, Yaling; Brandt, Bernd W.; Yang, Jingmei; Chen, Yu; Buijs, Mark J.; Crielaard, Wim; Cheng, Lei; Deng, Dongmei (Frontiers in Microbiology, 2019)
Objectives: Our aim of this work was to investigate the regrowth of implant-related biofilms after various antimicrobial treatments in vitro. Methods: Saliva-derived microcosm biofilms were grown on titanium discs in an active attachment model. Treatments including hydrogen peroxide (HP), citric acid (CA), chlorhexidine (CHX) and distilled water (control), at different concentrations, were applied to 2-day biofilms for 1 or 5 min. The viability, lactic acid production, and composition of the biofilms were followed for 3 days. The biofilm composition was analyzed by 16S rDNA amplicon sequencing. Results: The short treatments of CA, CHX, and HP resulted in a 2−3 log reduction in biofilm viability and lactic acid production immediately. However, both parameters returned to the pre-treatment level within 2 days due to biofilm regrowth. The alpha diversity of the regrown biofilms in antimicrobial-treated groups tended to decrease, whereas the diversity of those in the water-treated group increased. The composition of the regrown biofilms altered compared to those before treatments. Streptococcus and Enterobacteriaceae were enriched in the regrown biofilms. Conclusions: Although the antimicrobial treatments were efficient, the multi-species biofilms were indeed able to regrow within 2 days. The regrown-biofilms display an altered microbial diversity and composition, which in the oral cavity may lead to an aggressive infection.